Improved protocol for aseptic collection and handling procedures of bovine blood diet in areas with special contamination challenges for use in tsetse rearing - Kibugu, J. K.; Kiragu, Japhet M.; Mumba, A.M.; Mwangangi, D.M.; Muchiri, M. W. (SAGE Publications, 2010)
Importation of blood to support tsetse feeding in Africa is costly and marred by delays, quarantine restrictions and other logistic problems,while chemical contamination is likely to be encountered in tsetse diet from drug residues arising from treatment of animal diseases in Africa.Further, blood diet collection procedures are not standardized risking the health of the donor animals. We established a blood collection procedure of bovine blood for in vitro tsetse feeding in areas with special contamination challenges that is safe for both donor animals and tsetse flies.